Design and Experiment of Orchard Air-Assisted Sprayer with Airflow Graded Control - Fan Feng; Hanjie Dou; Changyuan Zhai; Yanlong Zhang; Wei Zou; Jianjun Hao (Agronomy)
The orchard air-assisted sprayer exhibits strong droplet penetration, allowing uniform adhesion on both the front and back surfaces of leaves. The spray deposition and spray drift are influenced not only by the amount of pesticide but also by the airflow provided by the air-assisted system. To meet the requirements for regulating airflow and pesticide application in orchards, a method based on the iris structure for continuous adjustment of the air inlet area was proposed. An airflow control mechanism for orchard air-assisted sprayers, which is easy to install, was developed, and a circular recirculating pressure-stabilized spray system was designed. Additionally, an orchard sprayer supporting graded airflow control was developed. Experiments were conducted to assess airflow variation within the tree canopy and the spray deposition and spray drift under different airflow levels. The results showed that the average airflow attenuation rates in the canopy were 63.0%, 71.8%, and 82.5% for the leaf areas and canopy thicknesses of 826.5 cm2, 1409.8 cm2, and 1931.1 cm2, and 1.5 m, 2.0 m, and 2.5 m, respectively. Graded variable control of airflow based on canopy variation helps improve droplet uniformity within the canopy and reduce spray drift in non-target areas. When the airflow in the middle of the tree canopy exceeds 1.50 m/s, the spray deposition ratio on both sides of the leaves increases to 83.55%, and the coefficient of variation in the droplet deposition on both sides is less than 33.24%. These findings provide support for pesticide precision application and spray drift control in orchards.